2024
DOI: 10.12968/jowc.2024.33.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a kinesio-taping-based treatment in stage IV sacral pressure ulcers in older patients: a pilot study

Giorgio Badino,
Nicola Veronese,
Alberto Cella

Abstract: Objective: As reduced tissue vascularity is one of the mechanisms that prevent skin ulcers from healing, treatments that can improve local circulation could accelerate their clinical resolution. Given that kinesio-taping (KT) can improve tissue blood circulation and lymphatic drainage, we aimed to determine whether applying KT close to stage IV pressure ulcers (PUs) could improve their healing. Method: Older patients with stage IV sacral PUs, and impaired mobility and functional dependency who were consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…KT exerts several beneficial effects on muscle function, including reduced pain, decreased muscle fatigue, and increased ROM[ 21 ]. A previous study showed that KT can increase the subcutaneous space and subsequently improve blood circulation and lymphatic drainage[ 22 ]. Another study found that combination therapy with MLD and KT yielded more promising results in alleviating pain and edema than a single therapy[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…KT exerts several beneficial effects on muscle function, including reduced pain, decreased muscle fatigue, and increased ROM[ 21 ]. A previous study showed that KT can increase the subcutaneous space and subsequently improve blood circulation and lymphatic drainage[ 22 ]. Another study found that combination therapy with MLD and KT yielded more promising results in alleviating pain and edema than a single therapy[ 23 ].…”
Section: Discussionmentioning
confidence: 99%